(untitled) (Groundings Undergraduate, 2026)
This essay aims to report on any connections between Eurpides’ tragedies and opera over its 500 year history. I will begin by laying out the thematic concerns that are central to Euripides’ writing as the summaries his tragedies that have most often been adapted to opera, which are including but not limited to Medea, Alcestis, and the Bacchae. This argument will focus on key operas that connect the art form to Euripides, mostly by being direct adaptations of one or more plays, such as Lully’s Alceste, Cherubini’s Medea, and Wellesz’s Alkestis. Any diversions from the source material, whether thematic or narrative, will then be assessed and accounted for within the wider musical and historical context. This will determine that, as I hypothesise, the extent to which the plays of Euripides had a place in shaping the development of Western opera was significant.